Sodobne informacijske tehnologije in storitve: OTS 2018: zbornik triindvajsete konference, 19. in 20. junij 2018 (University of Maribor Press, 2018)
Advanced Information Technology and Services: OTS 2018: Proceedings of the Twenty-Third Conference, 19th -20th of June, 2018. The papers in the proceedings of the 23rd Professional Conference on Advanced Information Technology and Services address the extremely topical challenges that we (IS/IT experts, software engineers, computer scientists, data scientists, software and solution architects, developers, IT managers, etc.) encounter in our daily work. The authors present innovative solutions and rich experience gained by conducting real-life projects: using blockchain technologies and platforms, establishing new ecosystems, business models and services contributing to digital transformation, introducing and implementing micro-service architectures, ensuring security, confidentiality and privacy, and related risk-management techniques, providing full virtualization and exploitation of infrastructure, updating and upgrading existing information systems, integrating machine learning algorithms and intelligent services and big data platforms, developing and using web components and technologies, applying agile approaches that enable the rapid and efficient development of both prototypes and production-oriented user-centric solutions via automated processes and continuous integration, delivery & deployment.